2022
DOI: 10.7150/jca.74829
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Traditional Chinese Medicine Combined with Systemic Therapy on Patients with Liver Cancer: A Systemic Review and Network Meta-analysis

Abstract: Objective: As immune combination therapy in the treatment of liver cancer made significant achievements, and the modulating effect of traditional Chinese medicine (TCM) on immunity gradually appeared. The main purpose of this study was to study the effect of different TCM combined with systemic therapy (ST) on immune regulation in patients with liver cancer, as well as the efficacy and safety of combined therapy, and to find the best combined application scheme by ranking. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…At present, the mechanism of this synergy is still unclear. However, in previous studies, it has been reported that Chinese medicine could regulate immune function ( 32 - 34 ). In the primary research, we found that the ratio of the spleen to organ increased after the intervention of Chinese medicine, while since the spleen contains many immune cells, the intervention of Chinese medicine may regulate the immune function.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the mechanism of this synergy is still unclear. However, in previous studies, it has been reported that Chinese medicine could regulate immune function ( 32 - 34 ). In the primary research, we found that the ratio of the spleen to organ increased after the intervention of Chinese medicine, while since the spleen contains many immune cells, the intervention of Chinese medicine may regulate the immune function.…”
Section: Discussionmentioning
confidence: 99%
“…KAI, one of the traditional injections of Chinese medicine, exhibits excellent anti-tumor activity and synergistic effects of chemotherapeutic drugs in various solid tumors (Cang et al, 2022;Pu et al, 2022). However, the possible mechanism of KAI in cancer therapy remains obscure.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hepatocellular carcinoma who receive Huaier can extend their recurrence-free survival and reduce their risk of extrahepatic recurrence (Zhang et al, 2021;Li et al, 2022;Luo and Hu, 2023). In addition, adjuvant therapy with Huaier can significantly improve immune function as well as conventional anticancer therapies' efficacy and safety (Pu et al, 2022). In the treatment of breast cancer, conventional treatment combined with Huaier significantly improved overall remission and the health-related quality of life for patients compared to that obtained via conventional treatment alone (Yao et al, 2020), and Huaier adjuvant therapy has also been shown to improve immunity and enhance sensitivity to radiotherapy (Zhang et al, 2019;Li et al, 2020) (Table 1).…”
Section: The Use Of Huaier In the Clinical Treatment Of Breast Cancermentioning
confidence: 99%